In Midsummer Days : And Other Tales. - Strindberg, August (The Floating Press, 2014)
For readers who are familiar with Swedish writer August Strindberg's early, groundbreaking works for the stage, the dreamy magical realism of the short story collection In Midsummer Days will likely come as a surprise. These tales veer sharply away from the unflinching realism that came to be associated with Strindberg in the early twentieth century. Nonetheless, though they represent a dramatic shift in style, the tales in this collection are sure to engage and enchant.